The “gray zone” in pediatric end-of-life care: bioethical and medico-legal reflections - Scendoni, Roberto; De Micco, Francesco (Frontiers in Pediatrics, 2025)
Palliative care for children with incurable diseases represents one of the most complex challenges in pediatric medicine. It requires a delicate balance between continuing potentially ineffective therapies and ensuring comfort and dignity during the terminal phase. Decisions involve both the family and the medical team, with a particular focus on the “gray zone,” where prognostic uncertainty makes it difficult to determine the most ethical course of action. According to the WHO, palliative care aims to improve the quality of life for both the child and their family, addressing not only physical pain but also psychological and social issues. This article explores the bioethical and medico-legal implications surrounding end-of-life care, parental decision-making autonomy, and the need to always prioritize the child's best interests, while respecting their dignity and values.